A Fourier method for the determination of focus for telescopes with stars. Issue 2 (27th January 2022) - Tan, C Y; Schulz, B
ABSTRACT: We introduce a Fourier method (Fm) for the determination of best focus for telescopes with stars. Our method fits a power function, that we will derive in this paper, to a set of images taken as a function of focuser position. The best focus position is where the power is maximum. Fm was first tested with small refractor and Schmidt–Cassegrain telescopes. After the successful small telescope tests, we then tested Fm with a 2 m Ritchey–Chrétien–Coudé. Our tests show that Fm is immune to the problems inherent in the popular half-flux diameter method.